Employee Performance in Indonesian Companies: Work Environment, Training & Career Development, and Rewards & Recognition as Antecedents - Putri, Maria Ervania Eka; Ahwallia, Ananda Putri; Radhiya, Fabian Narmada; Octaviyana, Frisca; Putri, Safir Dzakiyyah Aziziyah (Journal of Business, Management, and Social Studies, 2022)
The purpose of the study was to find out which antecedent has the greatest impact on employee performance: work environment, training and career development, or rewards and recognition. The data collection technique uses random sampling which produces data from the perspective of people who are experienced as employees of a company or organization with expectancy theory as the base measurement of the analysis. The findings revealed that work environment had the biggest influence on employee’s work performance, while training and career development did not. The suggested employee performance study will contribute to the growing body of knowledge aimed at understanding behavior of employees in Indonesia.